Paul-Elder Based Student Worksheet as an Evaluation Tool and Development of Critical Thinking Skills: an Experimental Study in High School - Anggreani, Ina; Sumarni, Woro; Kadarwati, Sri (International Journal of Active Learning, 2024)
Critical thinking skills are essential for addressing 21st-century challenges. In the field of education, learning systems are designed to enhance students' abilities to analyze information, evaluate arguments, and make well-reasoned decisions based on rational and logical thinking. This study aims to examine the differences in the application of Paul-Elder-based student worksheets (LKPD) in improving students' critical thinking skills. This research employed an experimental method, using a control group that received Problem-Based Learning (PBL) worksheets and an experimental group that received Paul-Elder-based worksheets as a special treatment. Critical thinking skills data were collected through pre-tests, post-tests, and student worksheets (LKPD). The results showed that the experimental group experienced a more significant improvement in critical thinking skills compared to the control group. The improvement pattern in the experimental group was more systematic, particularly in problem identification, information gathering, and concept comprehension. However, a decline was observed in the conclusion-drawing stage, indicating that students still struggled to formulate accurate conclusions. Meanwhile, in the control group, critical thinking skills developed but followed a less consistent pattern.